New Plant Reports from the State of Karnataka - Udayan, P. S.; Ravikumar, K.; Udaiyan, K. (Indian Forester, 2004)
Detailed botanical studies conducted in 9 Medicinal Plants Conservation Areas (MPCAs), located in Karnataka state have resulted in the collection of many interesting plants. After critical study, 12 of them Including 2 exotic naturalized species are new distribution record to Karnataka State.